2008
DOI: 10.1002/gps.2042
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG in progressing vs stable mild cognitive impairment (MCI): results of a 1‐year follow‐up study

Abstract: qEEG revealed decreased alpha activity in progressing MCI and mild AD prior to an increase of slow wave activity, which typically occurs in advancing AD. This finding may reflect an affection of thalamo-cortical relay activity and cortical connectivity in the early disease course of AD. Reduced alpha activity in MCI subjects at baseline may have prognostic value regarding future cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 37 publications
4
63
1
1
Order By: Relevance
“…Brainwave components of the resting EEG could be altered in the early stages of AD. There is evidence that EEG power in the alpha band declines with AD-related cognitive impairment [293]. Other studies have shown enhanced low-frequency brain oscillation in the theta [294] and delta bands in temporal and occipital areas as well as reduction of beta power in temporal and occipital areas in MCI [295].…”
Section: Resting-state Neuroelectrical/neuromagnetic Markersmentioning
confidence: 98%
“…Brainwave components of the resting EEG could be altered in the early stages of AD. There is evidence that EEG power in the alpha band declines with AD-related cognitive impairment [293]. Other studies have shown enhanced low-frequency brain oscillation in the theta [294] and delta bands in temporal and occipital areas as well as reduction of beta power in temporal and occipital areas in MCI [295].…”
Section: Resting-state Neuroelectrical/neuromagnetic Markersmentioning
confidence: 98%
“…The main effects are summarized as follows: 1) combined alpha-theta power density and mean frequency from left temporal-occipital regions [316]; 2) anterior localization of alpha sources [315]; 3) high temporal delta sources [378]; 4) high theta power density [379]; and 5) low posterior alpha power density [380]. …”
Section: Contribution and Role Of Electroencephalography (Eeg)mentioning
confidence: 99%
“…EEG biomarkers are optimal for screening purposes because the EEG recording can be obtained using relative cheap and non-invasive equipment, which is widely available and fast to use. Several previous EEG studies of conversion from mild cognitive impairment to Alzheimer's disease have been conducted (Jelic et al, 1996, 2000; Huang et al, 2000; Stam et al, 2003; Schoonenboom et al, 2004; Rombouts et al, 2005; Babiloni et al, 2006, 2011; Kwak, 2006; Rossini et al, 2006, 2008; Lehmann et al, 2007; Moretti et al, 2007a, b, 2008, 2011; Luckhaus et al, 2008) mainly using biomarkers such as spectral measures and synchronization between brain regions. Machine-learning techniques have been used to explore differences between MCI and AD with varying success (Huang et al, 2000; Bennys et al, 2001; Prichep et al, 2006; Buscema et al, 2007; Lehmann et al, 2007; Prichep, 2007; Rossini et al, 2008), however, only few studies have tried to predict the conversion from MCI to AD (Prichep et al, 2006; Prichep, 2007; Antila et al, 2013).…”
Section: Introductionmentioning
confidence: 99%